2018
DOI: 10.1017/s1742170518000558
|View full text |Cite
|
Sign up to set email alerts
|

Crop–livestock integration in smallholder farming systems of Goromonzi and Murehwa, Zimbabwe

Abstract: Poor productivity in smallholder farming systems has necessitated research on the potential of crop–livestock integration to sustainably improve productivity. The study hypothesized that improvement in individual agronomic and livestock systems and synergistic utilization of by-products of either system increases productivity, profitability and integration. Smallholder farming households were classified into: old and resource endowed (OR); part time (PT); and young, risk-taking and enthusiastic (YRE) following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This, according to Kreitler et al [ 30 ], is critical to enhance their understanding of the various dimensions of these integrated crop-livestock innovations and how they can play a part in supporting the functions along various value chain pillars. Mkuhlani et al [ 12 ] also reported the need for human capital development programs which can unlock the entrepreneurship capacity of small-scale farmers.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This, according to Kreitler et al [ 30 ], is critical to enhance their understanding of the various dimensions of these integrated crop-livestock innovations and how they can play a part in supporting the functions along various value chain pillars. Mkuhlani et al [ 12 ] also reported the need for human capital development programs which can unlock the entrepreneurship capacity of small-scale farmers.…”
Section: Resultsmentioning
confidence: 99%
“…There are several strategies that farmers can adopt to face climate change, contrasting vulnerabilities, and insecurities. Some of these strategies have been scientifically proven to work well by many research institutes such as CIMMYT [ 12 , 13 ]. Among the most notable climate change, adaptation and welfare security-enhancing strategies are the adoption of drought-resistant crops and crop varieties, and the rearing of drought-tolerant livestock types and breeds.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations